Common characteristics of successful endurance programs - Gibbons, T. (2006)
Internationally successful endurance athletes are the product of genetic ability and many years of systematic training. Inherited endowment and the genetic ability to positively adapt to training are important considerations when discussing endurance performance; however, training of the genetic gifts at certain stages of growth and development may ultimately be more important. At the current level of international competition in endurance sport, one can only succeed after years of effective training, regardless of innate ability. There are many common characteristics that are attributed to the development of internationally successful endurance athletes. These factors include: